Fakta Cerita dan Fakta Sosial dalam Film "Jumbo" 2025 oleh Ryan Andriandhy: Tinjauan Sosiologi Sastra - Alfarizqo, Muhammad; Khoiri, Abdul Aziz (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2025)
Film serves as a form of literary presentation on the screen. It represents one of the most effective modern literary media for depicting societal conditions (Sayoga, 2020). Abrams proposes an approach to literary works grounded in objective principles, with an emphasis on literary structure (Teeuw, 2017). A key research concept within the sociology of literature is Emile Durkheim's theory of social facts. Social facts are defined as ways of acting, thinking, and feeling that are external to the individual and possess a coercive power (Adam, 2024). Durkheim categorizes social facts into two types: material and non-material. This study examines the forms of story facts based on Abrams' model and Emile Durkheim's social facts as depicted in the 2025 film *Jumbo*. This research employs a descriptive qualitative method. The primary data source is the 2025 film "Jumbo" by Ryan Andriandhy, with data consisting of transcripts of dialogue, transcripts of conflict scenes, and documentation transcripts. Data collection techniques involved observation and documentation utilizing the script transcript of the film "Jumbo" (2025). The findings reveal Abrams' story facts, encompassing characters and characterization, plot, and setting. Additionally, Emile Durkheim's social facts are identified, including material social facts (local shops, radio, and civic laws) and non-material social facts (morality, collective consciousness, collective representation, and anomie). These findings are correlated with real-world conditions.